2015
DOI: 10.1080/02640414.2015.1012099
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and physical performance characteristics of top-elite, elite and non-elite youth female team handball players

Abstract: In order to maximise the potential for success, developing nations need to produce superior systems to identify and develop talent, which requires comprehensive and up-to-date values on elite players. This study examined the anthropometric and physical characteristics of youth female team handball players (16.07 ± 1.30 years) in non-elite (n = 47), elite (n = 37) and top-elite players (n = 29). Anthropometric profiling included sum of eight skinfolds, body mass, stature, girths, breadths and somatotype. Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2
13

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 26 publications
7
66
2
13
Order By: Relevance
“…As the sport-specific skill of throwing or shooting a ball involves the transfer of forces via a kinetic chain, those junior ball players with increased muscle mass may be able to deliver a handball at higher velocities. However, these findings should be interpreted with caution, as the summary conclusion includes relationships from only one study [63].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…As the sport-specific skill of throwing or shooting a ball involves the transfer of forces via a kinetic chain, those junior ball players with increased muscle mass may be able to deliver a handball at higher velocities. However, these findings should be interpreted with caution, as the summary conclusion includes relationships from only one study [63].…”
Section: Discussionmentioning
confidence: 84%
“…Of the 41 studies included in the review, only one study was interventional in design [54], with the remaining observational in nature. Research in handball [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] was the most frequently included teambased, ball sport followed by volleyball [69][70][71][72][73][74][75][76][77][78][79][80]. Other sports investigated included soccer [81][82][83][84][85][86], basketball [87][88][89][90], netball [91,92], lacrosse [93], and softball [94].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also few reports on ball velocities in handball throws in adolescent players. Even though one study has reported an average throwing velocity as high as 108 km/h in adolescent male players, most studies have reported that adolescent male players' throws involve a ball speed between 72-86 km/h (15)(16)(17)(18) and female players between 65-83 km/h (19,20).…”
Section: Shoulder-specific Demandsmentioning
confidence: 99%